Strenuous Exercise-Induced Tremendously Elevated Transaminases Levels in a Healthy Adult: A Diagnostic Dilemma - Prabin Khatri; Aryan Neupane; Suman Raj Sapkota; Bibhav Bashyal; Dipesh Sharma; Ashmita Chhetri; K. C. Chirag; Ashish Banjade; Priyanka Sapkota; Subarna. Bhandari (Case Reports in Hepatology)
The liver function test (LFT) is a commonly performed test in clinical practice in order to assess well-being of the liver; however, derangement in liver enzymes, however, may not necessarily imply an underlying liver pathology. The standard liver function test measures alanine aminotransferase (ALT), aspartate aminotransferase (AST), alanine phosphatase (ALP), bilirubin levels (total, direct, and indirect), proteins (total protein and albumin), and PT-INR (prothrombin time and international normalized ratio). In addition to common causes, liver enzyme levels can also be elevated due to extrahepatic causes, such as muscular injury can elevate transaminases levels. Here in, we present a case of an asymptomatic healthy male who was doing vigorous exercise and presented with reports of elevated transaminase levels. During evaluation of the case, most of his reports came to be within normal range. Additionally, when reevaluated after discontinuation of vigorous exercise, 3 weeks later and then a month later, his liver enzyme levels were observed to be within normal range. Hence, we suspect that muscle damage-induced transaminitis might not have been considered in the differential diagnosis during the evaluation of a patient with raised transaminases levels and also suggest that it should be kept as a differential in the given scenario.